Wpływ prawa żywnościowego - Gadbin, Daniel (Wydawnictwo Naukowe UAM, 2010)
At the crossroads of different fields (public law and private law, commercial law and environmental protection law, spatial planning law, etc.), agricultural law is becoming increasingly influenced by food law, which is no longer limited to the traditional principles of hygiene. This emerging field of law is poorly known, little taught, considered to be of little interest for legal studies, particularly in France. This discussion was limited to the investigations of the double effect of the European food law on agricultural law: in the scope in which it attempts to incorporate into its structure one of the previous structural elements of agricultural law (the structural effect) and in the scope, in which food law changes considerably the focus of agricultural law on consumer protection (the effect of the content). In the conclusion the Author discusses e.g. the necessity to develop subtle compromises between agricultural law being forced onto the defensive and food law in the offensive. The European Commission is ready to provide CAP with a more social aspect and acknowledging the right to food as one of the principal rights in Europe may provide important support for the development of CAP.

A cavallo tra diverse discipline (del diritto pubblico e del diritto privato, del diritto commerciale e del diritto ambientale, del diritto della sistemazione spaziale etc.) il diritto agrario subisce attualmente una forte influenza dal diritto alimentare, poiché quest’ultimo non si limita più a enucleare principi in tema di igiene alimentare. Il diritto alimentare è una disciplina recente, pertanto, poco conosciuta, insegnata, e attraente per le analisi giuridiche, soprattutto in Francia. Le considerazioni condotte si limitano all’analisi del doppio impatto che il diritto alimentare europeo ha sul diritto agrario. In particolare il diritto alimentare toglie al diritto agrario un elemento della sua struttura (impatto strutturale), inoltre orienta il diritto agrario verso la tutela del consumatore (impatto testuale). Secondo l’Autore vi è la necessità di elaborare dei sensibili compromessi tra il diritto agrario e il diritto alimentare. La Commissione Europea è pronta a dare alla PAC una dimensione sociale. Inoltre il riconoscimento del diritto al cibo come diritto fondamentale può essere un alleato importante per lo sviluppo della PAC.